Contingencies of value : alternative perspectives for critical theory - Smith, Barbara Herrnstein (Cambridge, Mass. : Harvard University Press, 1991)
Charges of abandoned standards issue from government offices; laments for the loss of the best that has been thought and said resound through university corridors. While revisionists are perplexed by questions of value, critical theory--haunted by the heresy of relativism--remains captive to classical formulas. Barbara Herrnstein Smith's book confronts the conceptual problems and sociopolitical conflicts at the heart of these issues and raises their discussion to a new level of sophistication.

Polemical without being rancorous, Contingencies of Value mounts a powerful critique of traditional conceptions of value, taste, judgment, and justification. Through incisive discussions of works by, among others, David Hume, Immanuel Kant, Northrop Frye, Georges Bataille, Jacques Derrida, Richard Rorty, and Jürgen Habermas, Smith develops an illuminating alternative framework for the explanation of these topics.

All value, she argues, is radically contingent. Neither an objective property of things nor merely a subjective response to them, it is the variable effect of numerous interacting economies that is, systems of apportionment and circulation of "goods." Aesthetic value, moral value, and the truth-value of judgments are no exceptions, though traditional critical theory, ethics, and philosophy of language have always tried to prove otherwise.

Smith deals in an original way with a wide variety of contemporary issues--from the relation between popular and high culture to the conflicting conception of human motives and actions in economic theory and classical humanism. In an important final chapter, she addresses directly the crucial problem of relativism and explains why a denial of the objectivity of value does not--as commonly feared and charged--produce either a fatuous egalitarianism or moral and political paralysis.
Keywords: vrednovanje; teorija književne kritike; estetika